Built environmental correlates of older adults' total physical activity and walking: a systematic review and meta-analysis - David W. Barnett; Anthony Barnett; Andrea Nathan; Jelle Van Cauwenberg; Ester Cerin; on behalf of the Council on Environment and Physical Activity (CEPA) (BMC, 2017)
Abstract Background Identifying attributes of the built environment associated with health-enhancing levels of physical activity (PA) in older adults (≥65 years old) has the potential to inform interventions supporting healthy and active ageing. The aim of this study was to first systematically review and quantify findings on built environmental correlates of older adults' PA, and second, investigate differences by type of PA and environmental attribute measurement. Methods One hundred articles from peer-reviewed and grey literature examining built environmental attributes related to total PA met inclusion criteria and relevant information was extracted. Findings were meta-analysed and weighted by article quality and sample size and then stratified by PA and environmental measurement method. Associations (p < .05) were found in relation to 26 individual built environmental attributes across six categories (walkability, residential density/urbanisation, street connectivity, access to/availability of destinations and services, infrastructure and streetscape, and safety) and total PA and walking specifically. Reported individual- and environmental-level moderators were also examined. Results Positive environmental correlates of PA, ranked by strength of evidence, were: walkability (p < .001), safety from crime (p < .001), overall access to destinations and services (p < .001), recreational facilities (p < .001), parks/public open space (p = .002) and shops/commercial destinations (p = .006), greenery and aesthetically pleasing scenery (p = .004), walk-friendly infrastructure (p = .009), and access to public transport (p = .016). There were 26 individual differences in the number of significant associations when the type of PA and environmental measurement method was considered. No consistent moderating effects on the association between built environmental attributes and PA were found. Conclusions Safe, walkable, and aesthetically pleasing neighbourhoods, with access to overall and specific destinations and services positively influenced older adults' PA participation. However, when considering the environmental attributes that were sufficiently studied (i.e., in ≥5 separate findings), the strength of evidence of associations of specific categories of environment attributes with PA differed across PA and environmental measurement types. Future research should be mindful of these differences in findings and identify the underlying mechanisms. Higher quality research is also needed.